Medical Prescription Formula: Structural and Linguistic Standardization - O. Yu. Vasilyeva (Научный диалог, 2021)
The traditions of medical prescription design, motivated by the universal-semiotic meaning of Latin as a pharmaceutical metalanguage is examined in the article. The author dwells on the interpretation of the methods of prescribing and linguistic representation of different types of drugs: mixtures, powders, ointment-based drugs and drugs in tablet form. The standardization of text-forming parameters of a medical prescription has been established, which are determined both by its compositional-structural organization and linguistic formula. A comparative characteristic of constant linguistic units (lexical, morphological, syntactic), fixed in ancient prescription recipes and fixed in medical prescriptions of modern times, is offered. The lexico-semantic composition of a medical prescription is determined by a set of stable expressions that have received a formulaic representation to express the methods of administration, control the dosage of a medicinal product, and the mandatory nature of a medical prescription. The dominant methods of verbal-predicative and case-fixed word usage, which are basic for the grammar of the Latin language, are described. The clichéd syntactic constructions still preserved in modern medical prescriptions, which have a specific deictic function, addressed by the doctor to both the pharmacist and the patient (imperative, conjunctive), have been identified. In the final postulates, the author’s functionally conditioned typology of means of expressing linguistic formulaality is presented.